Vocational High School Students’ Anger Management Skill - Anifa Tuzzuhroh Nurbaiti; Budi Astuti; Prisa Sari Yantika (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2020)
The present study aimed to describe students’ anger management based on its aspects. Applying descriptive quantitative approach,  the present study involved 280 students of SMK Muhammadiyah Mungkid who were recruited using simple random sampling technique.  The data were collected using anger management scale and analyzed using descriptive statistics. The present study showed that students’ overall anger management skill was categorized as very high. In terms of anger management aspects, students’ anger recognition, anger control, anger relief, and assertive anger expression skills were categorized as high, high, moderate, and high, respectively. The result of the present study is expected to serve as a preliminary study for school counselors to determine appropriate techniques to help students to improve anger management skills.